If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3(w-4))/4-6=-3
We move all terms to the left:
(3(w-4))/4-6-(-3)=0
We add all the numbers together, and all the variables
(3(w-4))/4-3=0
We multiply all the terms by the denominator
(3(w-4))-3*4=0
We calculate terms in parentheses: +(3(w-4)), so:We add all the numbers together, and all the variables
3(w-4)
We multiply parentheses
3w-12
Back to the equation:
+(3w-12)
(3w-12)-12=0
We get rid of parentheses
3w-12-12=0
We add all the numbers together, and all the variables
3w-24=0
We move all terms containing w to the left, all other terms to the right
3w=24
w=24/3
w=8
| 67=7x+2.5x | | 2x2x25/5x=1 | | 10-3x=5x-8 | | 10x=5x-50 | | 2.5x-9.05=7.7 | | 5x+10=12.5 | | (2/4)x/2+6(x5-1)=54x+60/2 | | (5|)^(x+2)-5^x=4.8 | | 0-6y=18 | | 5x-2+4=3(8-5x) | | 5x-2/3+4=8-5x | | 6x/x+17-1=0 | | (0.25)^(2-x)=8^x| | | 3x^2-18x-420+20=0 | | X³+4x-40=0 | | |9-6x|=4 | | 5x-3=7x9 | | y=3-2/3*5 | | 3k-10=-2 | | y=3-2/3(5) | | 4a+3a+8=16 | | 5a-4a+6=8 | | 14+5a=12a+1 | | 2a+3=10-3a | | 14m+3m=12 | | 7+3m+m=19 | | 2a+3=9-3a | | 3a-2a+1=2 | | -4(x+7)-45=2-55 | | 5+2g+g=41 | | 2g+g=24 | | 5x-2x-4=5 |